Advanced perspective on heavily phosphorus-doped diamond layers via optical emission spectroscopy - Kil-dong Sung; Stefan Andrei Irimiciuc; Michal Novotný; Zdeněk Weiss; Pavel Hubík; Jaromír Kopeček; Martin Vondráček; Vincent Mortet (APL Materials)
Although heavily phosphorus-doped diamond (PDD) holds great potential for advanced device applications, incorporating phosphorus into diamond remains challenging with conventional growth methods. In this study, optical emission spectroscopy (OES) was used to correlate the emission intensity ratio of PH to CH radicals (IPH/ICH) with phosphorus concentration ([P]) in diamond layers synthesized under varying phosphine ([PH3]/[H2]) and methane ([CH4]/[H2]) concentrations using microwave plasma-enhanced chemical vapor deposition. OES results revealed a strong proportional relationship between IPH/ICH and [P] across different [PH3]/[CH4] ratios. However, beyond a maximum [P] of ∼7.0 × 1020 atoms/cm3, further increases in IPH/ICH did not lead to higher [P] with a significant reduction in phosphorus incorporation efficiency (η), consistent with the solubility limits of phosphorus in diamond. At lower [PH3]/[H2], [P] did not scale proportionally with [PH3]/[CH4], exhibiting nonlinear behavior due to phosphorus contamination (Pcont.) in the reaction chamber, which provided sufficient PHx radicals to grow heavily PDD without PH3 gas flow. By understanding plasma properties and their effects on [P], heavily PDD has been effectively achieved with enhancing [P] (up to 745%) and η (up to 143%) by alternating the dominant radical species in the plasma. Time-dependent control of precursor gas flow allowed modulation of IPH/ICH, improving control over phosphorus incorporation. This novel growth approach offers valuable insights for optimizing PDD synthesis, enabling more efficient phosphorus incorporation for electronic, electrochemical, and quantum applications.